1998
DOI: 10.1002/(sici)1098-2337(1998)24:4<287::aid-ab4>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Acute social stress and cardiac electrical activity in rats

Abstract: Take-down policyIf you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…As demonstrated in a previous study, the mere presence of a potentially antagonist individual in the home cage elicits a strong psychosocial stress response (elevation of plasma corticosterone levels) in both aggressive and nonaggressive resident rats [29]. Moreover, cardiac autonomic reactivity during psychosocial stress test (adverse social contact without overt fighting) in intruder rats was shown to be as large as during an actual fight experience [30]. Continuous ECG, T and LOC recordings were performed in baseline conditions (30 min, prior to the test), during the test (15 min) and throughout the recovery period (45 min).…”
Section: Methodssupporting
confidence: 53%
“…As demonstrated in a previous study, the mere presence of a potentially antagonist individual in the home cage elicits a strong psychosocial stress response (elevation of plasma corticosterone levels) in both aggressive and nonaggressive resident rats [29]. Moreover, cardiac autonomic reactivity during psychosocial stress test (adverse social contact without overt fighting) in intruder rats was shown to be as large as during an actual fight experience [30]. Continuous ECG, T and LOC recordings were performed in baseline conditions (30 min, prior to the test), during the test (15 min) and throughout the recovery period (45 min).…”
Section: Methodssupporting
confidence: 53%
“…In rats, Sgoifo et al (49) reported that defeat induced a higher increase in plasma catecholamine concentration than restraint. These authors reported that defeat resulted in a high risk of ventricular arrhythmias (49,50). Therefore, the lack of heart injury in fighting mice may not be attributed to a lack of catecholamine stimulation of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…The IC 50 for ErbB1 is 100,000 times lower than that for related tyrosine kinases (HER2-Neu or platelet-derived growth factor receptor) (32). This inhibitor was shown to delay A431 tumor growth in nude mice (7) and to decrease hydroxyproline accumulation in a rat model of pulmonary fibrosis (46).…”
Section: Discussionmentioning
confidence: 99%
“…Social stressors often involve aggressive interactions between dominant and subordinate animals and are widely used to study the effects of stress on animal behavior and physiological functioning [51][52][53][54]. Social disruption involves aggressive interactions between a dominant intruder mouse (i.e., the aggressor) and resident subordinate mice (i.e., the experimental subjects).…”
Section: Studies Involving Repeated Social Defeatmentioning
confidence: 99%